Virtuelle Wirklichkeiten Atmosphärisches Vergangenheitserleben im Digitalen Spiel - Zimmermann, Felix (Büchner-Verlag, 2023)
Atmospheres are everywhere: at the workplace, in the soccer stadium, in front of the crackling fireplace. They shape our everyday language and have become quite natural expressions of how we find ourselves in certain environments and how we feel about them. Their influence is far-reaching: aesthetic atmospheres are closely linked to a contemporary experience-oriented historical culture whose products and practices claim to establish an immediate contact with the past. With ›Vergangenheitsatmosphären‹ Felix Zimmermann offers for the first time a term to adequately describe this striving for immediacy. By means of in-depth analyses of the digital games »Anno 1800« (2019), »Assassin's Creed Syndicate« (2015), and »Dishonored: The Mask of Wrath« (2012), the term is contoured and the productivity of atmospheric research trained on theories and methods of public history, game studies, and phenomenology is demonstrated.